CHARACTERISTICS OF ADVERSE EVENTS OF CORONAVIRUS DISEASE 2019 VACCINES FIRST, SECOND AND BOOSTER - Wiwiek Probowati; Tejo Jayadi; Brenda Miriane Rustam (Berkala Ilmiah Kedokteran Duta Wacana, 2023)
Background Coronavirus Disease 2019 (COVID-19)  was a new type of highly contagious disease that had a high risk of developing Acute Respiratory Distress Syndrome (ARDS). According to the World Health Organization (WHO), COVID-19 can be transmitted mainly through aerosol particles contiguous to another human in one meter. To cope with this pandemic, the government programmed vaccinations around the world, including in Indonesia. Objective This study provided new information about the description of the characteristics of adverse events following vaccination participation in vaccination COVID-19 first, second and booster doses. Method This descriptive research was conducted using a cross-sectional method. Subjects were populations with various characteristics at Bethesda Hospital, Bethesda Lempuyangwangi Hospital, and the Jawa Dayu Christian Church who had received the COVID-19 vaccine. The data were univariately presented as a distribution table using the IBM  SPSS - Statistical Program for Social Science Statistics 23. Result From 400 respondents, the most common types of vaccine received during the first dose were Sinovac, the second dose of Sinovac,  and the Moderna for booster dose. Conclusion The first dose was the same as the second dose. Most felt drowsiness 87.9%, swelling and pain at the injection site 77.9%, and weakness at 60.4%.   In phase 1 clinical research of the mRNA vaccine from Moderna, side effects occurred in more than 50% of vaccination participants in the form of fatigue, chills, headache, myalgia, and pain at the injection site, especially at higher doses.